Colposcopy in evaluation of suspected cervical cancer: a prospective, observational study - Desai, Ashwini Sudhir; Panchbudhe, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical cancer is the fourth most frequent cancer in women according to World Health Organization. In India the incidence is approximately 1 in 53 compared with 1 in 100 women in more developed regions of the world. Cervical cancer is eminently preventable by early detection using various screening tests like Pap smear, colposcopy, HPV testing. In this study we aim to evaluate the use of colposcopy in early detection of cervical cancer and also assess risk factors for the same. Primary objective was to study the correlation between colposcopic findings and histopathological analysis with a secondary objective to assess risk factors for development of cervical neoplasia. Methods: The study was carried over a period of 2 years (October 2016 to October 2018) with a sample size of 60 in the department of obstetrics and gynecology at tertiary care centre. Participants who fit the inclusion criteria were included in the study after taking a written and informed consent. The colposcopy findings were correlated with the histopathological findings of the cervical biopsy that was undertaken. Results: Colposcopy impression had sensitivity of 93.8% in predicting the histopathology, specificity was 77.3%, positive predictive value was 60%, negative predictive value was 9% and the diagnostic accuracy was 81.7%. On analyzing the risk factors, it was found that the odds of malignant histopathology were 0.55 times decreasing with each unit increase in age (at first intercourse) (p value<0.05). Conclusions: Colposcopy gives immediate and accurate results and its value as a diagnostic test is undisputable. The sensitivity of colposcopy is high and hence in high risk population or remote places where women do not turn for regular screening tests, colposcopy can be used primarily as the screening test.